Recent developments concerning the application of the Mannich reaction for drug design. (2nd January 2018) - Biersack, Bernhard; Ahmed, Khursheed; Padhye, Subhash; Schobert, Rainer
ABSTRACT: Introduction : The versatile multicomponent Mannich reaction occupies a salient position in organic chemistry and drug design. Sound knowledge of its scope and variations and of the biological activities of Mannich bases is crucial for the development and improvement of drugs for various diseases. Areas covered : The following article provides an overview of the latest developments in the field of drugs based on the Mannich reaction. Web-based literature searching tools such as PubMed and SciFinder were applied to obtain useful articles. In addition, pertinent literature that was recently published by the authors is discussed in this manuscript. The chemical structures of bioactive Mannich bases are also given. Expert opinion : The Mannich reaction represents a feasible and cost-effective procedure with great potential for drug development. Several newly discovered Mannich bases exhibit sound activities against various human diseases as well as favorable pharmacokinetics. Thus, scientific research about Mannich bases is prospering and appears very attractive both for chemists and for clinicians.